Analisis Strategi Pemasaran dalam Upaya Meningkatkan Minat Pembelian PT. Emma Tour and Travel - Tengku Kespandiar (Jurnal Syntax Transformation, 2022)
This study aims to identify and analyze: (1) The marketing strategy applied by PT. Emma Tour And Travel in an effort to increase purchase interest, (2) Buying interest analysis at PT. Emma Tours And Travels. (3) the obstacles faced by PT. Emma Tours And Travels. This study uses a qualitative descriptive method is a survey research, because this research provides a clear and systematic description of the marketing strategy of PT. ocean star space tour and travel Banjarmasin. and research methods documentation, observation, interviews. Based on the results of the research on the 4P Marketing Strategy (Product, Price, Place, Promotion) in increasing consumer buying interest implemented by PT. Emma Tour And Travel Malang uses a strategy that is on products, prices, promotions, and places. And the results of the study found that the average reason for consumers to make purchases at PT. Emma Tour And Travel Malang is because of the price, and the service provided. This identifies the leaders in order to understand what can increase purchase intention in order to pay more attention to these variables